Colloidal Dual-Diameter and Core-Position Controlled Core/Shell Cadmium Chalcogenide Nanorods - Kim, Dahin; Lee, Young Kuk; Lee, Dongkyu; Kim, Whi Dong; Bae, Wan Ki; Lee, Doh C. (AMER CHEMICAL SOC, 2017)
To capitalize on shape- and structure-dependent properties of semiconductor nanorods (NRs), high-precision control and exquisite design of their growth are desired. Cadmium chalcogenide (CdE; E = S or Se) NRs are the most studied class of such, whose growth exhibits axial anisotropy, i.e., different growth rates along the opposite directions of {0001} planes. However, the mechanism behind asymmetric axial growth of NRs remains unclear because of the difficulty in instant analysis of growth surfaces. Here, we design colloidal dual-diameter semiconductor NRs (DDNRs) under the quantum confinement regime, which have two sections along the long axis with different diameters. The segmentation of the DDNRs allows rigorous assessment of the kinetics of NR. growth at a molecular level. The reactivity of a terminal facet passivated by an organic ligand is governed by monomer diffusivity through the surfac'e ligand monolayer. Therefore, the growth rate in two polar directions can be finely tuned by controlling the strength of ligand ligand attraction at end surfaces. Building on these findings, we report the synthesis of single-diameter CdSe/CdS core/shell NRs with CdSe cores of controllable position, which reveals a strong structure optical polarization relationship. The understanding of the NR growth mechanism with controllable anisotropy will serve as a cornerstone for the exquisite design of more complex anisotropic nanostructures.
Keywords: QUASI-TYPE-II; SEMICONDUCTOR QUANTUM RODS; CDS NANORODS; ENERGY-TRANSFER; CDSE/CDS NANOCRYSTALS; POLARIZED EMISSION; CONTROLLED GROWTH; LIGAND-BINDING; SHAPE CONTROL; HETEROSTRUCTURES